Diversity of classic and novel human astrovirus in outpatient children with acute gastroenteritis in Shanghai, China - Lu, Lijuan; Zhong, Huaqing; Xu, Menghua; Jia, Ran; Liu, Pengcheng; Su, Liyun; Cao, Lingfeng; Zhu, Xunhua; Xu, Jin (Frontiers in Microbiology, 2023)
Human astrovirus (HAstV) plays a crucial role as a pathogen in acute gastroenteritis (AGE) among children. This study aimed to investigate the diversity and epidemiology of classic and novel HAstV in outpatient children aged 0-16 years with AGE in Shanghai. From May 2020 to December 2022, a total of 1482 stool samples were collected from children diagnosed with AGE at the Children's Hospital of Fudan University. HAstV was identified using pan-astrovirus consensus primers. Over the study period, 3.3% (49/1482) of specimens tested positive for HAstV, with a detection rate of 2.5% (37/1482) for classic HAstV and 0.8% (12/1482) for novel HAstV. Among the 12 cases of novel HAstV, 11 (91.7%) belonged to HAstV-MLB, and 1 (8.3%) was HAstV-VA. Genotyping revealed the presence of six circulating genotypes.HAstV-1 was the most prevalent among the study population, with a detection rate of 1.8% (26/1482), followed by HAstV-MLB1 (0.7%, 10/1482) and HAstV-4 (0.6%, 9/1482). Notably, all detected HAstV-4 strains in this study exhibited a high degree of sequence identity (99.0%-100.0%) with an astrovirus strain previously isolated from Bactrian camels. This study found HAstV in all age groups, with the highest detection rate of HAstV-positive specimens observed in children older than 73 months (5.7%, 12/209). In conclusion, this study provides valuable insights into the molecular epidemiology of both classic and novel HAstV. It is noteworthy as it simultaneously characterizes and reports their presence for the first time in Shanghai.